Characterisation and rescue of a recombinant newcastle disease virus strain AF2240-I - Kavitha, Murulitharan (2016)
Newcastle disease virus (NDV) or avian paramyxovirus 1 remains a constant major threat to commercial poultry production. The virus has shown remarkable effect as an oncolytic agent as well as a promising vaccine candidate against animal diseases. Although various studies have produced positive response rates for these two applications, there are still some important issues to be addressed which requires reverse genetics application. The rescue of a Malaysian NDV would help in the development of a recombinant vaccine; one which is phylogenetically closer to those viruses from current outbreaks with a potential to be used as a novel oncolytic agent. One such candidate strain with these potentials is the strain AF2240-I, a derivative of the viscerotropic velogenic local NDV strain AF2240. The main objectives of this study are to sequence the full genome of NDV strain AF2240-I and perform in-silico characterisation and to generate a reverse genetics system to rescue stably virulent NDV strain AF2240-I. Firstly, full genome amplification was performed using PCR and rapid amplification of cDNA ends (RACE) method followed by sequencing to verify the sequence. Full length sequence analysis showed that the strain AF2240-I belongs to genotype VIII at a length of 15,192 bp which follows the rule of six. The amplification of the haemagglutinin-neuraminidase (HN) gene of the strain given (initially presumed AF2240) has indicated the presence of Arg 403 residue in the HN gene which was reported to be absent in the HN gene of strain AF2240. A frameshift was also observed between the amplified matrix (M) gene of AF2240-I and the published M gene sequence of AF2240. It was concluded from that the frameshifts in both HN and M gene were likely due to quasi-species interference. Meanwhile, rescue of virus was done using the helper plasmid method. Three helper plasmids consisting of nucleoprotein (NP), phosphoprotein (P) and large protein (L) genes were prepared in pCI-Neo expression vector. The full length NDV anti-genome was synthesized and cloned into a transcription vector, pOLTV_phiX. The synthesised genome contained a silenced BsmBI RE site, at position 6741, by replacing G with A (CGTCTC to CATCTC) to serve as a genetic marker. These plasmids (helper plasmids & full genome plasmid) were co-transfected into Baby Hamster Kidney (BHK) cells stably expressing T7 RNA polymerase by lipofectamine transfection reagent using 5 different ratios and harvested at different time. The recombinant AF2240- I (rAF) recorded an intracerebral pathogenicity index (ICPI) and mean death time (MDT) values between 1.83 - 1.85 and between 47 h to 49 h respectively for passage 1 to passage 5. In summary, 16 h post transfection is sufficient to produce infectious viral particles in cell supernatant and that all 5 ratios showed no preference in the production of AF2240-I infectious virus particles. Also, both pathogenicity indices showed that rAF possesses a stable virulence capability even after 5 passages. Thus the reverse genetics system of a local NDV strain AF2240-I was successfully achieved.